2022
DOI: 10.3390/agronomy12051224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvest Date on Kernel Quality and Antioxidant Activity in su1 Sweet Corn Genotypes

Abstract: In order to achieve a high-quality product, sweet corn should be harvested at the optimal stage of maturity. The taste of sweet corn depends largely on the kernel moisture (KM) and total sugars (TS) content while its health properties are attributed to the content of total phenols (TPH) and antioxidant activity (AO). This study aimed to estimate quality in sugary (su1) sweet corn hybrids based on the maximum content of kernel chemical compounds and the content change during maturation. During two growing seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, no other natural or artificial sweetener can match sucrose's crucial functional qualities in a variety of food products [35]. Sucrose was the main soluble sugar, accounting for approximately 62% of the soluble sugars in the control baby corn sample (Table 1), which is less than the 66.4% and 77.1% reported by Ledenčan et al [36]. In contrast, sucrose comprised between 9.6% and 30% of the total soluble sugar recorded in the samples of popping, semi-flint and sweet baby corn with salt and the same samples with salt and sugar (Table 1).…”
Section: Chemical Composition Of Baby Corn Samplesmentioning
confidence: 78%
See 1 more Smart Citation
“…Additionally, no other natural or artificial sweetener can match sucrose's crucial functional qualities in a variety of food products [35]. Sucrose was the main soluble sugar, accounting for approximately 62% of the soluble sugars in the control baby corn sample (Table 1), which is less than the 66.4% and 77.1% reported by Ledenčan et al [36]. In contrast, sucrose comprised between 9.6% and 30% of the total soluble sugar recorded in the samples of popping, semi-flint and sweet baby corn with salt and the same samples with salt and sugar (Table 1).…”
Section: Chemical Composition Of Baby Corn Samplesmentioning
confidence: 78%
“…In support of this, the research by Zhu et al [37] found that sucrose content accounted for approximately 94%, 88%, and 85% of the soluble sugars in the different sweet corn genotypes. Generally, the content of each sugar, as well as the total sugar content, reach maximum levels at about 17 days after pollination and decrease during maturation [36]. The sucrose content in the control baby corn sample amounted to 17.79%, which was about 29-, 10-and 16-fold higher than that found in the popping, semi-flint and sweet baby corn samples with salt, respectively.…”
Section: Chemical Composition Of Baby Corn Samplesmentioning
confidence: 83%
“…While sweet corn carbohydrate traits are generally considered highly heritable due to the large effect of recessive endosperm mutations on these traits, carbohydrate traits are Crop Science also highly impacted by timing of harvest (Ledenčan et al, 2022;Szymanek, 2009). It is of interest in a breeding program to determine if a prediction model for carbohydrate traits calibrated with 1 year of data can be used to accurately predict a second year.…”
Section: Prediction Model Validationmentioning
confidence: 99%
“…In the following article, Ledenčan et al [23] estimated the quality at harvest of sweet corn hybrids (su1), based on the maximum content of compounds of biological interest in the grain (total phenolic compounds and antioxidant capacity) and the change in the content of the moisture of the grain and total sugars during ripening. In this sense, to achieve a high-quality food, sweet corn must be harvested at the optimal state of maturation.…”
Section: Evolution Of Compounds and Characteristics Of Crops During R...mentioning
confidence: 99%